SIRPα modulates the podocyte cytoskeleton through influencing the phosphorylation of FAK at tyrosine residue 597 - Xia Yuanyuan; Zhao Yue; Tian Jing; Yang Xue; Fan Yun; Dong Shihui; Yang Fan; Zhang Mingchao; Zeng Caihong (Acta Biochimica et Biophysica Sinica)
Signal regulatory protein α (SIRPα) is recognized as a significant transmembrane protein within the glomeruli that is specifically localized in podocytes, where it plays a role in modulating downstream signaling pathways through phosphorylation. Upon tyrosine phosphorylation of the immunoreceptor tyrosine-based inhibitory motif (ITIM) within SIRPα, protein tyrosine phosphatases are recruited to facilitate the dephosphorylation of downstream signals. Nevertheless, the specific downstream signaling pathways affected by this mechanism have yet to be elucidated. In this study, phosphoproteomic analysis is conducted on podocytes with SIRPα deficiency to identify proteins whose phosphorylation is regulated by SIRPα and the associated signaling pathways in human podocytes. The results reveal significant alterations in biological processes related to cytoskeleton arrangement and cytoskeleton protein binding. Specifically, an increase in FAK tyrosine phosphorylation at Y576 is identified as a potentially crucial signal of the influence of SIRPα on the podocyte cytoskeleton. Our study suggests that SIRPα may facilitate podocyte cytoskeleton rearrangement and migration through the Src/FAK/p38 MAPK signaling pathway. For the first time, we discover increased level of SIRPα, which is strongly linked to urinary protein, in the urine of patients with nephrotic syndrome (NS). Additionally, an increase in urinary FAK level is observed in NS patients, which is positively correlated with both urinary protein level and urinary SIRPα level. These findings suggest that SIRPα and FAK may serve as promising biomarkers for podocytopathies.